2016
DOI: 10.1111/ans.13821
|View full text |Cite
|
Sign up to set email alerts
|

Trends in publication of general surgical research in New Zealand, 1996–2015

Abstract: The quality and quantity of surgical research in New Zealand has substantially increased over the past two decades. These results reflect the successful growth of a culture of academic surgery and the ongoing support of partner organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Wells et al demonstrated a trend towards publication of higher-level evidence with an increase in median IF equivalent to the expected organic growth of journal IF. 4 New Zealand ranks 14th globally with respect to general surgical publications per 10 6 inhabitants from 2000 to 2005, whereas Australia, comparably, ranks 11th globally. 3 The development of guidelines including the Consolidated Standards of Reporting Trials (CONSORT) 7 and Preferred Reporting Items of Systematic reviews and Meta-Analyses (PRISMA) 8 Statements is reflective of the need for standardized approaches to rigorous reporting of medical research.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Wells et al demonstrated a trend towards publication of higher-level evidence with an increase in median IF equivalent to the expected organic growth of journal IF. 4 New Zealand ranks 14th globally with respect to general surgical publications per 10 6 inhabitants from 2000 to 2005, whereas Australia, comparably, ranks 11th globally. 3 The development of guidelines including the Consolidated Standards of Reporting Trials (CONSORT) 7 and Preferred Reporting Items of Systematic reviews and Meta-Analyses (PRISMA) 8 Statements is reflective of the need for standardized approaches to rigorous reporting of medical research.…”
Section: Resultsmentioning
confidence: 97%
“…Other studies that have investigated trends in publication of general surgical research demonstrated an improvement in data quality over time associated with an increased proportion of RCTs (26% versus 48%, p < 0.05) 9 . Factors that have contributed towards the trend in increasing research growth in the surgical field have previously been discussed 4,9,10 . There is a strong encouragement for participation for accreditation within departmental surgical units 11 and publications are highly encouraged from prevocational surgical trainees in order to meet prerequisites of applying for surgical training, which is similar across many medical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…The last 10 years has seen the development of many academic focused courses and themes within Australian based surgical training (19). Nowadays, there exists many a provision of surgical research grants from both RACS and subspecialty societies, most notably the Garnett Passe in ENT, providing the necessary financial support for trainees and fellows wishing to conduct either part or full-time research (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of surgical research, the translational impact of surgical trials on clinical practice is rarely evaluated, hampering optimal implementation and de-implementation of surgical interventions [9]. It was suggested that reducing low-value surgical interventions, based on high-quality evidence, can save €153 million per year in the United Kingdom alone [10][11][12][13][14]. High-quality surgical research has increased worldwide in the past decades [15].…”
Section: Introductionmentioning
confidence: 99%